Perlindungan Hukum Terhadap Beras Ase Lapang Pangkep Sebagai Produk Potensi Indikasi Geografis - Maemanah; Heliany, Ina; M, Nurmiati (Sawerigading Law Journal, 2023)
Legal protection for Pangkep Field Assets as a potential product of Geographical Indications, by knowing the role of the Pangkep government in encouraging efforts to protect Geographical Indications for Pangkep Field Assets, this research uses primary data and secondary data, then the data is analyzed descriptively qualitatively. The research results show that: 1) Pangkep field Ase has the potential to receive Geographical Indication Law protection because it has fulfilled the requirements for Geographical Indication registration such as characteristics and qualities that differentiate Pangkep field Ase from other rice, geographical environment, natural factors, human factors, area boundaries covered by the Indication Geography, history and traditions related to the use of Geographical Indications. However, to prove certainty, registration must be carried out first and must be tested by a team of Geographical Indication experts. 2) The Pangkep Regency Government has made efforts to provide Geographical Indication protection for the Pangkep field assets. However, the efforts made by the Pangkep Regency Government have not been optimal. This is due, among other things, to a lack of public awareness and understanding, especially farmers, of the importance of legal protection through Geographical Indications for Pangkep field assets.